2021
DOI: 10.1038/s41438-021-00518-x
|View full text |Cite
|
Sign up to set email alerts
|

A gene that underwent adaptive evolution, LAC2 (LACCASE), in Populus euphratica improves drought tolerance by improving water transport capacity

Abstract: Drought severely limits plant development and growth; accordingly, plants have evolved strategies to prevent water loss and adapt to water deficit conditions. However, experimental cases that corroborate these evolutionary processes are limited. The LACCASEs (LACs) family is involved in various plant development and growth processes. Here, we performed an evolutionary analysis of LACs from Populus euphratica and characterized the functions of LACs in Arabidopsis and poplar. The results showed that in PeuLACs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 59 publications
0
21
0
Order By: Relevance
“…Recently, LACs have been found to be involved in various abiotic stress responses in plants [49]. The overexpression of LAC2P can improve water transport, which leads to enhanced plant drought adaptation [59]. H 2 O 2 (hydrogen peroxide) is reported to be an important signaling molecule.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, LACs have been found to be involved in various abiotic stress responses in plants [49]. The overexpression of LAC2P can improve water transport, which leads to enhanced plant drought adaptation [59]. H 2 O 2 (hydrogen peroxide) is reported to be an important signaling molecule.…”
Section: Discussionmentioning
confidence: 99%
“…GhLAC4 knockdown plants showed lower lignin content and decreased G-lignin biosynthesis according to lignin content measurement, chemical staining, and GC/MS analysis. Although there are many LACs in plants, only a few of them participate in monolignol polymerisation into lignin ( Niu et al, 2021 ). For example, of 17 laccase genes in Arabidopsis , only LAC4 , LAC11 , LAC15 , and LAC17 were verified to act in lignin biosynthesis according to genetic analysis ( Liang et al, 2006 ; Berthet et al, 2011 ; Turlapati et al, 2011 ; Zhao et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Plant laccases (LAC, EC. 1.10.3.2), which belong to the blue copper oxidase/ρ-diphenol:dioxygen oxidoreductase family, are widely distributed in higher plants, including gymnosperms, monocots, and eudicots ( McCaig et al, 2005 ; Turlapati et al, 2011 ; Wang et al, 2014 ; Niu et al, 2021 ). In Arabidopsis , there are 17 known members of the laccase family, which are classified into six groups ( McCaig et al, 2005 ; Hoegger et al, 2006 ; Turlapati et al, 2011 ), of which eight are expressed in stems ( Berthet et al, 2011 ; Zhao et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, AtLAC14 and AtLAC15 were phylogenetically related to GhLAC1 and Gh-LAC15 in upland cotton, which have been demonstrated to be involved in positively regulating defense-induced lignification in the cell wall to enhance the broad-spectrum biotic stress response [12,13]. A recent study demonstrated that the overexpression of poplar PeuLAC2, which phylogenetically clustered with AtLAC14 and AtLAC15 of Arabidopsis, altered the xylem structure of plants, including thickening the secondary cell wall (SCW) and increasing the fiber cell length and stem tensile strength, and thereby mediated stronger antioxidant response and greater drought tolerance [44]. In our study, most CsLACs in subclade IV were remarkably upregulated in E. obliqua simulated feeding leaves.…”
Section: Discussionmentioning
confidence: 99%